A Bibliometric Analysis of Endoscopic Sedation Research: 2001–2020 - Qin, Yi; Chen, Sifan; Zhang, Yuanyuan; Liu, Wanfeng; Lin, Yuxuan; Chi, Xiaoying; Chen, Xuemei; Yu, Zhangjie; Su, Diansan (Frontiers in Medicine, 2022)
Abstract Background and Aims. To evaluate endoscopic sedation research and predict research hot spots both quantitatively and qualitatively using bibliometric analysis. Methods. We extracted relevant publications from the Web of Science Core Collection on 13 December 2020. We examined the retrieved data by bibliometric analysis (e.g. co- cited and cluster analysis, keyword co-occurrence) using the software CiteSpace and VOSviewer and the website of bibliometrics, the Online Analysis Platform of Literature Metrology (http://bibliometric.com/), to analyse and predict the trends and hot spots in this field. Results. We identified 2,879 articles and reviews on endoscopic sedation published between 2001 and 2020. Although the overall trend is increasing, with slight fluctuation in some years, there were significant increases in 2007 and 2012. In respect of the contributions on endoscopic sedation research, the United States (US) had the greatest number of publications, and it was followed by Japan and China. In addition, collaboration network analysis revealed that the most frequent collaboration was between the US and China. Six of the top ten most prolific research institutions were located in the US. The most publications on endoscopic sedation research in the past two decades were found primarily in journals on gastroenterology and hepatology. Keyword co-occurrence and co-citation cluster analysis revealed the most popular terms relating to endoscopic sedation in the manner of cluster labels; these included patient anxiety, tolerance, ketamine, propofol, hypoxia, nursing shortage, endoscopic ultrasonography, colorectal cancer, carbon dioxide insufflation and water exchange. Keyword burst detection suggested that propofol sedation, adverse event, adenoma detection rate (ADR), hypoxemia and obesity were newly-emergent research hot spots. Conclusions. Our findings showed that hypoxia, adverse event and ADR, along with conscious sedation and propofol sedation, have been foci of endoscopic sedation research over the past 20 years. The research focus has shifted from sedative drugs to sedative complications and endoscopy quality control, which means that there will be higher requirements and standards for sedative quality and endoscopy quality in the future.